Role Of Internet Of Things And Data Analysis On An Emerging Threat; Production (Cultivation) Of Curcuma Longa (Local Variety) In Krishnagiri District - N., Thangarasu; R , Rajalakshmi; K., Ramesh (International Journal of Psychosocial Rehabilitation, 2020)
In Indian agriculture is more scope for food production, but in real time, due to some natural disaster, it falls down. So using ICT technologies has to improve the cultivation. The data were collected from three varieties of Curcuma longa from 3 districts of turmeric-growing areas in Tamil Nadu. The Preparation of Hydroalcoholic Extracts of Curcuma longa. Then, analysis of phytochemicals varieties of Curcuma longa—to make the estimation of total phenols and total flavonoids of 3 varieties. In this estimation process, curcumin’s impact on factors such as geographic localization, harvest time, climate conditions, etc., on the phytochemical composition of turmeric rhizome.